2003
DOI: 10.1007/s11661-003-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of precyclic loading on stress-corrosion-cracking initiation in an X-65 pipeline steel exposed to near-neutral pH soil environment

Abstract: A study was carried out to understand the effect of precyclic loading on stress-corrosion-crack initiation in an X-65 pipeline steel exposed to a near-neutral-pH soil environment. The test specimens were precyclically loaded before corrosion exposure to represent a service history of up to about 20 years, depending on the severity of pressure fluctuation. Microcracks had initiated on the polished surface of the X-65 pipeline steel after long-time exposure at open-circuit potential (OCP) in a near-neutral-pH sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The X-65 pipeline steel was characterized as being susceptible to nearneutral pH SCC. [12,13,14] Compact tension (CT) specimens were machined from the X-65 pipe with the machined notch perpendicular to the circumferential direction of the pipe. Each of the specimens was polished to produce a scratch-free surface prior to mechanical loading.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-65 pipeline steel was characterized as being susceptible to nearneutral pH SCC. [12,13,14] Compact tension (CT) specimens were machined from the X-65 pipe with the machined notch perpendicular to the circumferential direction of the pipe. Each of the specimens was polished to produce a scratch-free surface prior to mechanical loading.…”
Section: Methodsmentioning
confidence: 99%
“…Crack initiation is also possible in near-neutral pH environments, even if the applied stress is low or not present. This occurs, for example, through galvanic corrosion at phase boundaries [12,14] or at mill scale/steel interfaces. [22,23] Nevertheless, a pre-existing axial crack would come to a dormant state under a monotonic loading in nearneutral pH environments.…”
Section: Existing Growth Modelsmentioning
confidence: 99%
“…Our findings further the understanding of the role of inhomogeneity of microstructure in SCC of a variety of pipe steels [11,12,18]. In the work of Kushida et al [11], steels of strength from APL 5 to X65 with ferrite-pearlite, ferritebainite, and bainites were tested in NS4 solution under a cyclic loading of stress ratio, R, of 0.7.…”
Section: Resultsmentioning
confidence: 63%
“…In a separate study of steels of strength level ranging from X52 to X100, Lu and Luo [12] concluded that a fine, uniform structure of bainite resisted SCC better than its ferrite-pearlite counterparts in their SSRT work. In a study on the effect of preloading, Chen et al [18] cyclically preloaded their test samples before starting SCC immersion tests and found preferential SCC cracks initiated from pits at metallurgical discontinuities such as grain boundaries, pearlitic domains, and banded phases in the steel. …”
Section: Resultsmentioning
confidence: 99%
“…However, a brief summary is made here for the purpose of better understanding the growth behavior of cracks beyond the dormant stage that is the focus of this paper. It is generally believed that crack initiation can be caused by many different mechanisms [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], including preferential dissolution at physical and metallurgical discontinuities such as scratches [12], inclusions [13], grain boundaries, pearlitic colonies and banded structures [14][15][16] in the steel; corrosion along persistent slip bands induced by cyclic loading prior to corrosion exposure [14,17]; crack initiation at stress raisers such as corrosion pits [18,19]; and localized corrosion through millscale-steel galvanic effects [20]. The initiation of microstructurally short cracks, usually less than 100 lm, can occur under a constant stress loading.…”
Section: Basic Considerationsmentioning
confidence: 99%